The Impact of Brexit on The Frequency of Road Transport to and from The UK Based on Research in A Transport Company - Marcin KŁAK (Communications of International Proceedings, 2023)
The purpose of this article is to examine the impact of the introduction of Brexit on the frequency of road transport to and from the UK based on a selected transport company. To achieve this goal, data directly from the studied company was used. In addition, the author conducted a systematic review of the literature on road transportation. The advantages and disadvantages of road transport were presented, and the changes that were introduced with Britain's exit from the European Union were pointed out, in particular, the documents required to cross the border were described. The main part of the study is devoted to examining the impact of Brexit on road transport in a selected transport company. The motivation behind conducting the study is the very limited literature on the subject of Brexit, which further enhances the validity of this research. A case study was chosen as the research methodology, detailing the research conducted at a selected transportation company. The results obtained allowed for a final discussion and conclusions.
Keywords: logistics; road transport; TSL; Brexit